Clinicopathologic Features and Outcome of Adenocarcinoma of the Anal Canal: A Population-Based Study. (13th May 2020) - Gogna, Shekhar; Bergamaschi, Roberto; Kajmolli, Agon; Gachabayov, Mahir; Rojas, Aram; Samson, David; Latifi, Rifat; Dong, Xiang Da
Abstract : Background . Anal canal adenocarcinoma (AA) is an uncommon tumor of the gastrointestinal tract. We seek to provide a detailed description of the incidence, demographics, and outcome of this rare tumor in the United States. Methods . The data on anal canal adenocarcinoma from SEER Program, between 1973–2015, were extracted. We analyzed the incidence rates by demographics and tumor characteristics, followed by analysis of its impact on survival. Results . The incidence of AA increased initially by 4.03% yearly from 1973 to 1985 but had a modest decline of 0.32% annually thereafter. The mean age for diagnosis of AA was 68.12 ± 14.02 years. Males outnumbered females by 54.8 to 45.2%. Tumors were mostly localized on presentation (44.4%) and moderately differentiated (41.1%). Age generally correlated with poor overall cancer survival. However, young patients (age <40 years) also showed poor long-term survival. Patients with localized disease and well-differentiated tumors showed better survival outcomes. Surgical intervention improved survival significantly as compared to patients who did not (116.7 months vs 42.7 months, p < 0.01 ). Conclusions . Anal canal adenocarcinoma demonstrated a poor bimodal cancer-free survival in both younger and older patient groups. Surgery significantly improves odds of survival and should be offered to patients amenable to intervention.